PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPA SD MELALUI MEDIA GAMBAR - Gebi Gebi (Dharmas Education Journal (DE_Journal), 2022)
The failure in the learning system is the absence of the use of learning media, both those that can be accessed at school and those planned by the instructor. The purpose of this study is to improve student learning outcomes in science learning through image media. This type of research uses Classroom Action Research (CAR) which intends to define the use of image media in increasing student learning outcomes in science subjects. The purpose of the preparation of this journal is to review that using image media is able to develop student learning outcomes in science learning in elementary schools. Data collection techniques are carried out through observation, tests, and documentation. The results showed that student learning outcomes progressed. From the results of the analysis, using image media can increase the learning outcomes of elementary school students in science learning, which at first had a completeness score of 3% to 96%, with an average of 43% to 83%.